2022
DOI: 10.3389/fped.2022.993460
|View full text |Cite
|
Sign up to set email alerts
|

#childhoodobesity – A brief literature review of the role of social media in body image shaping and eating patterns among children and adolescents

Abstract: Children’s food preferences are closely related to their parents’ food preferences and knowledge of food is linked to what their parents share with them. Parents, however, are not the only people who model such behavior. Paradoxically, the ubiquitous technological development can also pose a huge threat. In developed countries, 94% of teenagers use social media platforms such as: Instagram, Snapchat, Facebook, or TikTok, and this also applies to children. It can therefore be argued that parents’ nutritional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…The emerging findings in the review align with those of previous works on the topic (Modrzejewska et al, 2022;Revranche et al, 2022). Most studies (n = 15) have found a correlation among the variables under consideration: the time spent using social networks, the problematic usage of these platforms, the type of activities conducted on social media, and body dissatisfaction.…”
Section: Discussionsupporting
confidence: 82%
“…The emerging findings in the review align with those of previous works on the topic (Modrzejewska et al, 2022;Revranche et al, 2022). Most studies (n = 15) have found a correlation among the variables under consideration: the time spent using social networks, the problematic usage of these platforms, the type of activities conducted on social media, and body dissatisfaction.…”
Section: Discussionsupporting
confidence: 82%
“…Horiuchi et al (2020) have examined the effects of media use on children's sleep patterns and its correlation with psychosocial symptoms, underscoring the possible adverse effects of excessive media usage. Additionally, Modrzejewska et al (2022) looked into how electronic media affected kids' eating habits, body image, and health-related quality of life. They emphasized the necessity for interventions to address the detrimental effects of media exposure on kids' health.…”
Section: Challenges With Children's Health Related To Using Electroni...mentioning
confidence: 99%
“…Cuesta et al, ( 2018) and Modrzejewska et al, (2022) both reviewed the literature on the positive and negative effects of social media on adolescent body image and eating behaviors. However, it was assumed that adolescence with emotional intelligence traits contribute to positively identifying these behaviors, whereas the opposite is true.…”
Section: Body Image and Emotional Intelligencementioning
confidence: 99%